Frictional Wear Stability Mechanisms Of An Activated Carbon Composite Derived From Palm Kernel By Phase Transformation Study - Mahmud, Dayang Nor Fatin; Abdollah, Mohd Fadzli; Masripan, Nor Azmmi; Tamaldin, Noreffendy; Amiruddin, Hilmi (Emerald Group Publishing Limited, 2017)
Purpose – The purpose of this paper is to investigate the mechanisms of frictional wear stability of an activated carbon composite derived from palm kernel using phase transformation study. Design/methodology/approach – The unlubricated sliding test was executed using a ball-on-disc tribometer at different loads with a constant speed, sliding distance and temperature. Findings – Results of this paper suggest that stability of friction and wear of the test materials are primarily due to the phase transformation of the composite surface layer. Research limitations/implications – However, the effectiveness of the transfer layer as a medium for low friction and wear is only limited at certain applied loads. Originality/value – This is the first study, to the authors’ knowledge, to find out the mechanisms of low frictional wear properties of an activated carbon composite derived from palm kernel using phase transformation study.